2018
DOI: 10.1177/0306419018783023
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of the conceive-design-implement-operate framework in a mechanical engineering capstone project

Abstract: The Conceive-Design-Implement-Operate framework was initiated around 20 years ago at Massachusetts Institute of Technology (MIT) in order to reform engineering education to cope with the latest needs and challenges available in the industry. MIT researchers thought of the set of skills that graduates would need to have upon graduation. Then they developed the framework and syllabus, and then ran it through pilot programmes to monitor and refine its underlying approaches. The framework takes into account studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For example, to utilize the CDIO TM framework to provide structure to a projectbased course or curriculum. A particularly successful example of a curriculum structure that illustrated the application of OBE and project-based learning is provided in (Yong Ze Siin et al, 2020). The authors utilized the CDIO TM approach to assist in the attainment of learning outcomes for an engineering capstone project course -which is a key outcome of an accredited engineering degree.…”
Section: Overarching Pedagogiesmentioning
confidence: 99%
“…For example, to utilize the CDIO TM framework to provide structure to a projectbased course or curriculum. A particularly successful example of a curriculum structure that illustrated the application of OBE and project-based learning is provided in (Yong Ze Siin et al, 2020). The authors utilized the CDIO TM approach to assist in the attainment of learning outcomes for an engineering capstone project course -which is a key outcome of an accredited engineering degree.…”
Section: Overarching Pedagogiesmentioning
confidence: 99%
“…Edström et al. 8,9 concluded that in spite of sharing core values, both frameworks have many differences. And, rather than playing a competitive role, they both complement each other.…”
Section: Introductionmentioning
confidence: 99%